2003
DOI: 10.1097/00005537-200301000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Transnasal Endoscopic Closure of Cerebrospinal Fluid Leaks

Abstract: Our method is effective and does not require adjuvant procedures or prolonged hospital stays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 7 publications
3
10
0
Order By: Relevance
“…23) Over recent decades, endoscopic endonasal approaches beyond the sellar region have become more widespread, thanks to the combined contributions of both neurosurgeons and otorhinolaryngological surgeons, 2,13,21) providing the opportunity to consider this technique as a possible option for post-traumatic CSF rhinorrhea. 8,9,[17][18][19]24) Many authors have recently reported the successful repair of osteodural defects of the anterior skull base using either a purely endoscopic or an endoscopic-assisted endonasal technique. 1,2,7-9,12,15,17-19) Nevertheless, the choice of the best surgical approach depends primarily on the etiology of the fistula, the main characteristics of the trauma and the anatomical features of the leak site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23) Over recent decades, endoscopic endonasal approaches beyond the sellar region have become more widespread, thanks to the combined contributions of both neurosurgeons and otorhinolaryngological surgeons, 2,13,21) providing the opportunity to consider this technique as a possible option for post-traumatic CSF rhinorrhea. 8,9,[17][18][19]24) Many authors have recently reported the successful repair of osteodural defects of the anterior skull base using either a purely endoscopic or an endoscopic-assisted endonasal technique. 1,2,7-9,12,15,17-19) Nevertheless, the choice of the best surgical approach depends primarily on the etiology of the fistula, the main characteristics of the trauma and the anatomical features of the leak site.…”
Section: Discussionmentioning
confidence: 99%
“…18) Transcranial approaches are recommended for cases involving extensive dural tears, large skull base defects, multiple fractures, and associated severe brain injuries, i.e., where the likelihood of recurrence is high. 8,21) On the other hand, the endoscopic endonasal technique has been seen to accomplish better results in the repair of more anteriorly located skull base fractures, presenting round, well-defined borders, small tears of the dura mater and, eventually, absence of concomitant brain injuries. 18,19) As a matter of fact, post-traumatic CSF leaks have been found to occur more frequently in those areas of the anterior skull base where the dura mater is strictly adherent to the bone, i.e., the cribriform plate and the anterior and posterior ethmoidal roof.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors report high success rates with successful primary repair in 90% or more of cases. [7][8][9] Potential benefits of an endoscopic transnasal approach rather than a transcranial approach is the minimally invasive procedure and a high success rate compared to the average success rate of 70% achieved with transcranial approach. 10 Achieving an effective repair of CSF fistula via a transcranial approach can be difficult and may be unsuccessful as the surgeon will in some patients not be able to accurately identify the site of the leak.…”
Section: Discussionmentioning
confidence: 99%
“…72,80 Various authors have successfully used different types of autologous and nonautologous grafts, such as a mucoperiosteal flap from the middle turbinate or septum or mucoperichondrial, osseous, cartilaginous, fat, muscular fascia, middle turbinate, or septum pedunculated graft, or any combination of these grafts. 1,3,11,13,15,22,[24][25][26]28,35,47,51,55,56,64,65,67,77,79,90,101,108 Another widely discussed issue in endoscopic transnasal repair is whether the grafts used for repair should be placed above (inlay) or beneath (onlay) the skull base defects. In a meta-analysis, Hegazy et al 53 found that both techniques yielded similar results.…”
Section: Surgical Managementmentioning
confidence: 99%